Performance and serum biochemical profile of broiler chickens supplemented with piper cubeba ethanolic extract - Rubio, M. S. [UNESP]; De Laurentiz, Antonio Carlos [UNESP]; Sobrane, Fst [UNESP]; Mello, E. S. [UNESP]; Filardi, R. S. [UNESP]; Silva, Mla; Laurentiz, R. S. [UNESP] (My University, 2019)
Piper cubeba is an Asian pepper used in popular medicine for its known antimicrobial, antiparasitic, and anti-inflammatory actions. The study evaluated the effects of dietary inclusion of Piper cubeba ethanolic extract (PE) as a replacement for anantibiotic growth promoter (AGP) on the performance and biochemical serum profile of 1- to 21-d-old broilers (Cobb®). Two hundred one-d-old broilers were housed in experimental battery cages and distributed in a completely randomized design. The following treatments were applied: negative control (NC) – basal diet; positive control (PC) – basal diet with addition of AGP; and the basal diet with inclusion of 0.17%, 0.34%, and 0.52% of PE (NCE1, NCE2, and NCE3, respectively). Growth performance, biochemical serum profile and internal organ weights were evaluated. Birds fed the AGP presented higher feed intake compared with the other treatments (p<0.05). The PC, NC, and NCE1 treatments presented higher weight gain compared with those fed NCE2 and NCE3 (p<0.05). The NC, NCE1, and NCE2 diets promoted better feed conversion ratio than the PC and NCE3 (p<0.05). Lower triglyceride serum levels were determined in broilers fed the NC and NCE1 diets. Amylase serum levels were lower in NCE1 and NCE2 treatments compared with the NC (p<0.05), whereas those obtained with the PC and NCE3 diets were not different (p>0.05) from the others. Organ relative weights were not influenced by the treatments. The inclusion of 0.17% of PE did not compromise the growth performance, biochemical serum profile or organ relative weights of 21-d-old broilers.
Keywords: Additives; Antibiotic growth promoters; Biochemical serum profile; Pepper